Proces doskonalenia chrześcijańskiego w "Enarrationes in Psalmos" św. Augustyna - Zagórski, Dariusz (Vox Patrum, 2025)
In his work Enarrationes in Psalmos, Augustine extensively addresses the issue of Christian perfection. Encouraging the audience of his homilies to grow in faith, he first points to the necessity of conversion, which allows one to embark on the path of spiritual progress. This conversion is to be accomplished through the struggle against evil and weaknesses, as well as against the hateful activity of Satan directed against humans. Breaking away from sin and reconciling with God enables one to rise from spiritual numbness to life, emerging from wickedness toward an existence marked by “light” and “righteousness.” This process of acquiring goodness takes place through the perfection of virtues and the fulfillment of good deeds. It is a stage of serving amid the hardships and experiences of daily life-persevering until its end. Saint Augustine considers the goal of Christian life and the greatest good to be attachment to God. This is to manifest in a close relationship with the Creator, advancing to friendship with Him, attaining the status of children of God, and achieving salvation. This publication aims to present the individual stages of a Christian’s pursuit of spiritual perfection. It seeks to convey the message on this topic contained in the Commentary on the Psalms, a special work that testifies to the responsibility of the shepherd proclaiming the Word of God for the sheep entrusted to him.